Testing of antiplasmodium activity substance from endophytic fungus of Artemisia annua L. - ., Wahyono; ., Pudjono; P., Widyati (Indonesian Journal of Pharmacy, 2010)
Malaria is a life-threatening disease caused by  Plasmodium parasites. The rapid  spread  of  malaria-quinoline  resistance  enforce  to  find  of  new  antimalaria drug. Artemisia annua L having artemisinin as secondary metabolites, has been used as antimalaria agent for long time. One of source of bioactive compound is endophytic fungus. This fungus can produce similar bioactive compound to host plant.  The  thin  layer  chromatography  result  showed  that  endophytic  fungusfrom   A.annua    had  similar  chromatogram  profile  with  artemisinin.  This metabolite  was  not  secreted  in  the  fermentation  medium,  but  was  kept  in  the fungus  mycelium.  The  result  of  the  haem  polymerization  inhibitory  activity assay  showed  that  this  secondary  metabolites  inhibited  the  haem polymerization.  Ethyl  acetate  extract  of  fungus  A  had  IC50  value  0.824  ±  2.89 μM  to  inhibit  the  haem  polymerization;  fungus  E  was  0.861±  2.43  μM;  and fungus F was 1.394 ± 3.73 μM.Key words : endophytic fungus, antiplasmodium, the haem polymerization, IC50